Interventional Physiatry: Need of the Day - Rashid, MA (Journal of Shaheed Suhrawardy Medical College, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14398 J Shaheed Suhrawardy Med Coll, 2012;4(2):38